Achyranthes aspera L. leaf extract induced anticancer effects on Dalton's Lymphoma via regulation of PKCα signaling pathway and mitochondrial apoptosis. (28th June 2021) - Singh, Rishi Kant; Verma, Praveen Kumar; Kumar, Amit; Kumar, Sandeep; Acharya, Arbind
Abstract: Ethnopharmacological relevance: Epidemiological studies promote the inclusion of natural-products in diet due to their inhibitory effects on various types of cancer. Among them, Achyranthes aspera L. (Family Amaranthaceae) is a medicinal plant in Ayurvedic pharmacopeia, found in India, Southeast Asia, America, and Sub-Saharan Africa. It is endowed with anti-inflammatory, anti-oxidant, and anti-cancer activities. However, its potential effect on Non-Hodgkin lymphomas (NHLs), has not yet been clarified. Aim of the study: In the present study, we aimed to investigate the effect of Achyranthes aspera L. leaf extracts on highly aggressive murine NHL called Dalton's Lymphoma (DL) in vitro and in vivo . Material and methods: GC-HRMS analysis was carried out for the identification of compounds present in A. aspera leaf extract. The cytotoxicity of various A. aspera leaf extracts was evaluated on DL cells by MTT assay. Chromatin condensation, nuclear fragmentation, and morphological changes were observed by microscopy technique. Flow cytometry was used to measure the changes in mitochondrial membrane potential (ΔΨm) and apoptosis. In addition, the expressions of apoptosis-related proteins were detected by western blotting. Meanwhile, the in vivo anti-tumor effect of leaf extract was tested in DL induced Balb/c mice. Result: GC-HRMS analysis of A. aspera methanolic leaf extract (AAML) revealed the presence of ten pharmacologically active compounds. The results showed that AAML suppressed cell proliferation, decreased mitochondrial membrane potential, changed the morphological structure, and induced apoptosis. Moreover, AAML could promote the release of cytochrome c by regulating Bcl-2 family proteins and then activated caspase-9/ -3 to triggered cell apoptosis. At the same time in DL cells treated with AAML, the protein kinase Cα (PKCα) pathway was inhibited in a concentration-dependent manner. Remarkably, in vivo, AAML mediated suppression of DL growth in Balb/c mice was accompanied by attenuation of the PKCα pathway and induction of apoptosis. Our result suggested that AAML promotes mitochondrial apoptotic cascade in DL cells by suppressing the PKCα signaling pathway. Conclusion: The study suggests that AAML could potently suppress DL progression by promoting apoptosis via mitochondrial-cascade and attenuation of the PKCα signaling pathway. Graphical abstract: Image 1